A Quality‐of‐Things model for assessing the Internet‐of‐Things' nonfunctional properties. Issue 8 (17th June 2019) - Qamar, Ayesha; Asim, Muhammad; Maamar, Zakaria; Saeed, Saad; Baker, Thar
Abstract: The Internet of Things (IoT) is in a "desperate" need for a practical model that would help in differentiating things according to their nonfunctional properties. Unfortunately, despite IoT growth, such properties either lack or ill‐defined resulting into ad hoc ways of selecting similar functional things. This paper discusses how things' nonfunctional properties are combined into a Quality‐of‐Things (QoT) model. This model includes properties that define the performance of things' duties related to sensing, actuating, and communicating. Since the values of QoT properties might not always be available or confirmed, providers of things can tentatively define these values and submit them to an Independent Regulatory Authority (IRA) whose role is to ensure fair competition among all providers. The IRA assesses the values of nonfunctional properties of things prior to recommending those that could satisfy users' needs. To evaluate the technical doability of the QoT model, a set of comprehensive experiments are conducted using real data sets. The results depict an acceptable level of the QoT estimation accuracy. Abstract : In this paper we present a novel approach for thing selection and recommendation in the context of IoT. The paper first discusses how things' non‐functional properties are captured into a QoT model based on the performance of things' duties in the form of sensing, actuating, and communicating. It, then, evaluates how fair the QoT properties' values of things are, so that fair competition between things' providers occurs. Different from other existing QoS prediction approaches, we address the problem of lack of data usage of things‐to‐evaluate.